Protocol to optimize the biobanking of ovarian cancer organoids by accommodating patient-specific differences in stemness potential - Fabian Trillsch; Bastian Czogalla; Fabian Kraus; Alexander Burges; Sven Mahner; Mirjana Kessler (STAR Protocols, 2023)
Summary: We present a protocol for effective biobanking of epithelial ovarian cancer organoids, considering the heterogeneous clinical presentation and high recurrence rates. Our protocol involves parallel testing of three media to identify patient-specific optimal conditions. We describe steps for tissue dissociation, differential seeding, organoid cultivation, and biobanking. We outline procedures for fixation, embedding, and staining for confocal imaging. Furthermore, we demonstrate that brief cultivation of isolates in 2D on plastic enhances organoid-forming potential in selected lines, expanding their application scope.For complete details on the use and execution of this protocol, please refer to Hoffmann et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.